Demokrasi Dan Otonomi Desa Dalam Proses Pemilihan Kepala Desa Pasca Reformasi - Ummah, Siti Muslikhatul; Setiyawan, Wahyu Beny Mukti; Suparwi, Suparwi; Fatimah, Siti (JURNAL USM LAW REVIEW, 2023)
The purpose of this research is to analyze the implementation of democracy and village autonomy in the process of village head elections. The election of a village head is one form of genuine and pure village autonomy and democracy. However, with the emergence of modern states, the independence and ability of rural communities to manage their affairs have diminished. This is closely related to the decentralization that occurs in unitary states such as Indonesia. In a unitary state, one of the central matters is legal affairs. Legal matters include regulating the election of village heads, as stipulated in Minister of Home Affairs Regulation No. 112 of 2014 concerning the Election of Village Heads. This research uses a normative juridical method. The research results explain that village head elections, based on rules from the central government cascaded down to the village level, become procedural in the implementation of village head elections. In fact, these rules lead to the phenomenon of husband and wife pairs running as village head candidates in the same village to avoid having a single candidate, thereby enabling the village head election to take place. Furthermore, violations of rules regarding village head elections are common, such as instances of money politics and the lack of neutrality among village officials, but there is no legal follow-up related to these violations. Tujuan penelitian ini untuk menganalisis pelaksanaan demokrasi dan otonomi desa dalam proses pemilihan kepala desa. Pemilihan kepala desa merupakan salah satu bentuk dari otonomi dan demokrasi desa yang asli dan murni. Namun dengan munculnya negara modern, kemandirian dan kemampuan masyarakat desa untuk mengatur urusan desanya mulai berkurang. Hal tersebut tidak lepas dengan adanya desentralisasi yang terjadi di negara kesatuan seperti Indonesia. Dalam negara kesatuan salah satu urusan yang menjadi urusan pusat adalah soal hukum. Urusan hukum tersebut tidak lepas dari urusan untuk mengatur pemilihan kepala desa sebagaimana terdapat pada Permendagri No 112 Tahun 2014 tentang Pemilihan Kepala Desa. Metode penelitian ini menggunakan yuridis normatif. Hasil penelitian menjelaskan bahwa pemilihan kepala desa yang berdasarkan aturan-aturan dari pemerintah pusat yang diturunkan hingga tingkat desa menjadi prosedural dalam pelaksaan pemilihan kepala desa. Bahkan aturan tersebut menimbulkan adanya fenomena pasangan suami istri yang maju sebagai calon kepala desa di desa yang sama untuk menghindari calon tunggal sehingga pemilihan kepala desa dapat dilaksanakan. Selain itu ternyata aturan mengenai pemilihan kepala desa juga banyak terjadi pelanggaran namun tidak ada tindak lanjut hukum terkait pelanggaran tersebut. Pelanggaran tersebut antara lain adalah adanya money politics dan ketidaknetralan perangkat desa.